A frequency up-conversion rotational energy harvester with auxetic structures for high power output. (1st April 2023) - Chen, Keyu; Fang, Shitong; Lai, Zhihui; Cao, Junyi; Liao, Wei-Hsin
Abstract: Rotational energy harvesters (REHs) have been explored to substitute conventional batteries for small electronic sensors. However, there still exists a challenge for REHs to scavenge sufficient energy under low-rotational-frequency excitations. In this paper, we propose a plucking REH with auxetic structures, which utilizes the frequency up-conversion and auxetic structures to enhance the power output of the rotational energy harvesting under low-rotational-frequency excitations. Finite element simulation is performed to analyze the performance of the proposed REH. The simulation results match well with the experimental ones. When the magnet distance is set to be 2.5 mm, the maximum power output of the auxetic plucking REH (APREH) is found to be 1.43 mW at 1.1 Hz, which is increased by 686% compared with the conventional plain plucking REH. In addition, compared with typical plucking REHs, the proposed APREH achieves the highest power output under low-rotational-frequency excitations, which validates the advantage of adopting auxetic structures in plucking REHs.